Complications of D-J Stent: Tragedy of Fragmentation- a Case Report (Bangladesh Journal of Urology, 2020)
Ureteric stents have been used since many years in urologic practice. Many complications encountered during its use.A 19 years old young man previously underwent an open nephrolithotomy in right side and URS with ICPL in left side to treat right renal stone & left lower ureteric stone, respectively on the same setting. Bilateral double J-stent had been inserted at that time to provide postoperative drainage. The patient never returned for follow-up or removal of the ureteral stents. Three years later, the patient presented with a 2-week history of left lumbar pain and lower urinary tract symptoms.Bangladesh Journal of Urology, Vol. 17, No. 2, July 2014 p.97-100